A Coat of Many Colors Dress Culture in the Young State of Israel - Helman, Anat (Academic Studies Press, 2011)
A Coat of Many Colors investigates Israel's first seven years as a sovereign state through the unusual prism of dress. Clothes worn by Israelis in the 1950s reflected political ideologies, economic conditions, military priorities, social distinctions, and cultural preferences, and all played a part in consolidating a new national identity. Based on a wide range of textual and visual historical documents, the book covers both what Israelis wore in various circumstances and what they said and wrote about clothing and fashion. Written in a clear and accessible style that will appeal to the general reader as well as to students and scholars, A Coat of Many Colors introduces the reader both to Israel's history during its formative years and to the rich field of dress culture.